Aflatoksin: Aspek kesehatan, metode reduksi dan deteksinya - Rosyunita Rosyunita; Setyaning Pawestri; Nurmi Hasbi; Adelia Riezka Rahim (Sasambo Journal of Pharmacy, 2023)
Food contaminant aflatoxin is a mycotoxin produced by Aspergillus flavus and A. parasiticus. This article aims to discover the pathophysiological, immunological, pharmacological, toxicity, and reduction and detection methods of aflatoxin. Kinds of literature were obtained from Research Gate, Pubmed, and Science Direct with the primary keyword â€œaflatoxinâ€. Pathophysiologically, aflatoxin-contaminated food has been proven to cause necrosis in liver cells, developing into liver cancer. Immunologically, aflatoxin decreases monocyte and dendritic cell phagocytosis, neutrophil cell ATP production, and pro-inflammatory cytokine synthesis. Aflatoxin toxicity is at the LD50 of 12-16 mg/kg b.w, causing death. Pharmacologically, 120-201 Âµg/kg b.w causes aflatoxicosis, in vivo studies indicated that NovaSil, Sulfarophan, and Monanthotaxis caffra leaf extract may reduce its toxicity. Aflatoxins are highly thermostable; hence, once food has been contaminated, they cannot be destroyed by normal cooking process. The control and reduction should be conducted in post-harvest handling, common physical means practiced are heating, drying, and smoking. Chemically using ozone, 0.5 sodium bisulfate, 1% sodium hydroxide, 5% acetic acid, and prochloraz. Biologically using Flavobacterium aurantiacum B-184, Bacillus velezensis DY3108, and, a consortium of Geobacillus and Tepidimicrobium bacteria. Aflatoxin can be detected using TLC, HPLC, MS, ELISA, and UHPLC-ESI MS/MS. The prevention of aflatoxin occurrence is done through good post-harvest handling, good manufacturing practices, and applying regulations accordingly to ensure food products and feed are at acceptable levels of aflatoxin.